L’ecologia politica di Giacomo Leopardi - Luisetti, Federico (Rivista Internazionale di Studi Leopardiani, 2021)
Under the influence of Jean-Jacques Rousseau, Giacomo Leopardi meditates through his prose, poems and theoretical reflections on the primal scene of the “state of nature”. I argue that this construction serves both as a philosophical tool and anthropological reference, and that it shapes Leopardi’s original naturalism and critique of European social thought.